DIAGNOSA KEMARJINALAN KELEMBAGAAN LOKAL UNTUK MENUNJANG PEREKONOMIAN RAKYAT DI PEDESAAN - ELIZABETH, ROOSGANDHA (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 8, No. 2 Juli 2008)
Failure of development in rural mirror marginalitically of local institute and brittle, which can depict influence affect crisis to national economy. Rural development program which less lift sovereignty (politics) socialism economic activity, uncared and also its rural resource interest factor represent its uncared evidence traditional institute and structure, and the rural economics too; so that progressively of brittle. All planner and organizer of development assessed less comprehend its important role of rural local institute to development of rural economics and agricultural sector in sustaining national economy. If this condition anticipated, efficacy transformation of local institute to economics of rural society includes; cover culture social typically can be existed, what supported powered of human resource and leadership factor as actor of progress activator.
Keywords: Marginalitically of Local Institute Concept, National Economy, Rural Resources.